A pituitary gene network linking vgll3 to regulators of sexual maturation in male Atlantic salmon - Ahi, Ehsan Pashay; Sinclair-Waters, Marion; Donner, Iikki; Primmer, Craig R. (Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology, 2023)
Age at maturity is a key life history trait and a significant contributor to life history strategy variation. The maturation process is influenced by genetic and environmental factors, but specific causes of variation in maturation timing remain elusive. In many species, the increase in the regulatory gonadotropin-releasing hormone 1 (GnRH1) marks the onset of puberty. Atlantic salmon, however, lacks gnrh1 gene, suggesting gnrh3 and/or other regulatory factors are involved in the maturation process. Earlier research in Atlantic salmon has found a strong association between alternative alleles of vgll3 and maturation timing. Recently we reported strong induction of gonadotropin genes (fshb and lhb) in the pituitary of Atlantic salmon homozygous for the early maturation allele (E) of vgll3. The induction of gonadotropins was accompanied by increased expression of their direct upstream regulators, c-jun and sf1 (nr5a1b) but the regulatory connection between vgll3 and these regulators has never been investigated in any organism. In this study, we investigated the potential regulatory connection between vgll3 genotypes and these regulators through a stepwise approach of identifying a gene regulatory network (GRN) containing c-jun and sf1, and transcription factor motif enrichment analysis. We found a GRN containing c-jun with predicted upstream regulators, e2f1, egr1, foxj1 and klf4, to be differentially expressed in the pituitary. Finally, we suggest a vgll3 and Hippo pathway -dependent model for transcriptional regulation of c-jun and sf1 in the pituitary, which may have broader implications across vertebrates. Peer reviewed